Modeling Skull Network Integrity at the Dawn of Amniote Diversification With Considerations on Functional Morphology and Fossil Jaw Muscle Reconstructions - Werneburg, Ingmar; Abel, Pascal (Frontiers in Ecology and Evolution, 2022)
One of the major questions in evolutionary vertebrate morphology is the origin and meaning of temporal skull openings in land vertebrates. Partly or fully surrounded by bones, one, two, or even three openings may evolve behind the orbit, within the ancestrally fully roofed anapsid (scutal) skull. At least ten different morphotypes can be distinguished in tetrapods with many modifications and transitions in more crownward representatives. A number of potential factors driving the emergence and differentiation of temporal openings have been proposed in the literature, but only today proper analytical tools are available to conduct traceable tests for the functional morphology behind temporal skull constructions. In the present study we examined the anatomical network in the skull of one representative of early amniotes, †Captorhinus aguti, which ancestrally exhibits an anapsid skull. The resulting skull modularity revealed a threefold partitioning of the temporal region indicating, in its intersection, the candidate position for a potential infratemporal opening. The framework of †C. aguti was then taken as a template to model a series of potential temporal skull morphotypes in order to understand how skull openings might influence the modular composition of the amniote skull in general. We show that the original pattern of skull modularity (†C. aguti) experiences comprehensive changes by introducing one or two temporal openings in different combinations and in different places. The resulting modules in each skull model are interpreted in regard to the feeding behavior of amniotes that exhibit the respective skull morphotypes. An important finding is the alternative incorporation of the jugal and pterygoid to different modules enforcing the importance of an integrated view on skull evolution: The temporal region cannot be understood without considering palatal anatomy. Finally, we discuss how to better reconstruct relative jaw muscle composition in fossils by considering the modularity of the skull network anatomy. These considerations might be relevant for future biomechanical studies on skull evolution.